2002
DOI: 10.1271/bbb.66.685
|View full text |Cite
|
Sign up to set email alerts
|

Phytotoxic Sesterterpene, 11-Epiterpestacin, fromBipolaris sorokinianaNSDR-011

Abstract: The structure of siccanol, a phytotoxic sesterterpene of fungal origin, was analyzed after chemical conversion by NMR spectroscopy. Siccanol was found to be an epimer of terpestacin that has been isolated from Arthrinium sp., and was thus renamed 11-epiterpestacin. Its stereochemistry was also identical with that of fusaproliferin, a structurally related mycotoxin from Fusarium proliferatum. Therefore, this sesterterpene may also be referred to as 24-deacetyl fusaproliferin. The phytotoxicity of 11-epiterpesta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
34
0
3

Year Published

2004
2004
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(37 citation statements)
references
References 11 publications
0
34
0
3
Order By: Relevance
“…A good illustration resides in the elucidation of the structure of the liminoid insect antifeedant azadirachtin. A recent example is a total synthesis reported by Chan and Jamison at MIT [168] that showed that the proposed structure 58 of siccanol [169] was incorrect and that the natural product is identical to (À)terpestacin (59). [161] By the mid-1980s, however, the isolation of some structurally related compounds began to suggest that some elements of the central core were inaccurate.…”
Section: Methodsmentioning
confidence: 99%
“…A good illustration resides in the elucidation of the structure of the liminoid insect antifeedant azadirachtin. A recent example is a total synthesis reported by Chan and Jamison at MIT [168] that showed that the proposed structure 58 of siccanol [169] was incorrect and that the natural product is identical to (À)terpestacin (59). [161] By the mid-1980s, however, the isolation of some structurally related compounds began to suggest that some elements of the central core were inaccurate.…”
Section: Methodsmentioning
confidence: 99%
“…16 The spectroscopic characteristics and the specific ro tation of the 11 epiterpestacin 2 isolated by us almost coincided with those reported in the literature. 17 The last component of the extract, compound 3, was identified as β nitropropionic acid, according to X ray diffraction data. 18 Compound 1 possesses an antimicrobial activity against Staphylococcus aureus and Bacillus subtilis (MIC = 12.5 µg mL -1 ) and exhibits a cytotoxic action on the developing eggs of sea urchin Strongylocentrotus intermedius (MIC 50 = 40 µg mL -1 ).…”
mentioning
confidence: 99%
“…However, when we obtained a sample of synthetic epi-C11-terpestacin it was determined that its spectra did not match that of isolated siccanol but rather that of terpestacin itself. 40 Macrocyclization via an intramolecular allylation, followed by methylation and α-oxidation led to the completed synthesis of terpestacin and epi-C11-terpestacin.…”
Section: Enantioselective Reactionsmentioning
confidence: 99%